2017
DOI: 10.1111/pbr.12459
|View full text |Cite
|
Sign up to set email alerts
|

Breeding apomictic bahiagrass (Paspalum notatum Flügge) with improved turf traits

Abstract: The development of a turf‐type bahiagrass could have a remarkable impact on the billion‐dollar turf industry in the south‐eastern United States. The goals of this study were to (i) select bahiagrass genotypes with improved turf attributes and (ii) determine the reproductive mode and seed fertility of selected genotypes. The population included mutants, wild types, hybrids and standard cultivars evaluated at two locations for two years. Morphological variation was observed and clonal repeatability (H2) ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
(91 reference statements)
1
17
0
Order By: Relevance
“…The correlation analysis indicated that prolific inflorescence production will result in greater bahiagrass seed yield, as previously reported (Adjei & Mislevy, 1987; Adjei et al., 1992), but smaller seed size and lower germination would be expected when more inflorescences are produced. The positive relationship between seed weight and germination reported here and in previous studies (Adjei et al., 1992; Gates & Burton, 1998; Zilli et al., 2018, 2019), together with high heritability for both traits (Rios et al., 2017; Zilli et al., 2019), will be of great utility for breeding purposes.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The correlation analysis indicated that prolific inflorescence production will result in greater bahiagrass seed yield, as previously reported (Adjei & Mislevy, 1987; Adjei et al., 1992), but smaller seed size and lower germination would be expected when more inflorescences are produced. The positive relationship between seed weight and germination reported here and in previous studies (Adjei et al., 1992; Gates & Burton, 1998; Zilli et al., 2018, 2019), together with high heritability for both traits (Rios et al., 2017; Zilli et al., 2019), will be of great utility for breeding purposes.…”
Section: Discussionsupporting
confidence: 68%
“…The University of Florida bahiagrass breeding program selected advanced tetraploid breeding lines that showed promise for extended forage production (Acuña et al., 2009; Acuña, Blount, Quesenberry, Kenworthy, & Hanna, 2011) and improved turf applications (Pereira et al., 2017; Rios, Blount, Kenworthy, Acuña, & Quesenberry, 2013; Rios et al., 2017). Argentine and the improved forage‐type hybrids were classified as obligate apomictic (Acuña et al., 2009), meaning that they only produce apomictic seed (exact clones of the mother plant).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Panicum maximum. [16][17][18][19][20] In apomictic Paspalum malacophyllum, aposporous embryo sac and parthenogenetic embryo development seem to outcompete the sexual pathway in relation to embryo sac growth rates and seed types formed. 19 Other factors such as gene deregulation and ploidy levels have also been suggested to promote aposporous embryo sac growth in Paspalum.…”
Section: Textmentioning
confidence: 99%
“…P. notatum is not the exception because low seed germination levels, due to seed dormancy, have been reported as an important limitation for its adoption as a forage species (West & Marousky, ). However, a high variability for seed set and germination have been observed in P. notatum , especially for sexually reproducing genotypes (Acuña, Blount, Quesenberry, Hanna, & Kenworthy, ; Acuña et al, ), which would be very useful for breeding programmes, especially taking into account the high heritability reported for seed set and seed emergence in the species (Rios et al, ).…”
Section: Introductionmentioning
confidence: 99%